Effect Of Advertising, Direct Marketing, Word Of Mouth And Personal Selling On Consumer Purchasing Decisions - Soehardi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this study is to analyze the effect of advertising, direct marketing, word of mouth and personal selling on consumer purchasing decisions for passenger ship tickets in Tanjung Pasir. The population in this study are all tourists who use sea transportation services from Tanjung Pasir beach to Untung Island. The sample used is purposive sampling with 155 respondents distributed questionnaires and 82 respondents returning. Quantitative research methods are used in this study with analysis of construct validity and reliability, discriminant validity, outer loading, collinearity statistics, path coefficients, R square and model fit. The results obtained that there is a significant effect of advertising on consumer purchasing decisions, direct marketing on consumer purchasing decisions, word of mouth on consumer purchasing decisions and personal selling on consumer purchasing decisions.